Adaptabilidad de diecisiete (17) variedades introducidas de Maíz Amarillo Duro a suelos ácidos zona de calzada - Provincia de Moyobamba - Abanto Flores, Moisés (2002)
The present thesis work was carried out in the peruvian rainforest, south america, in the FUNDAM !ands (fundación para el desarrollo agrícola de alto mayo, for its initials in spanish; foundation for agriculture development of the mayo river), located between moyobamba and rioja city in the "Fernando belaunde" north highway. this region is situated in the "alto mayo" valley and belongs to the calzada district, province of Moyobamba, Department of San Martin; geographically located between the following coordinates: west latituqe 76º 58' south latitude 8º 47' and 860 meters over sea leve!. Our aim is to evaluate the adaptability and yield of introduced varieties of maize compared with comercial genotypes (inia 602, pimte and 28 t excludes) and to determine the costs of productíon of the different treatments and the relationshíp between costs and benefits. The yield was evaluated with biometric and vegetative characteristics of the twenty tested treatments, using the design statistical block completely randomized (bcr) with twenty treatments and tour repetitions. the results were analyzed using the "f" test and the multiple "duncann test. The experimental soil belongs to the group of inceptisoles of flat and automated topography with the following characteristics: loamy franco texture of sour reaction (ph = 5.00), a content of organic matter of 6.53%, a total nítrogen contents of 0.326%, a phosphorus contents of 6 .. 08 ppm and avaijable potassium of 54.74 ppm. The distance between the furrows was 0.80 m and the distance between plants in ploghed and ranked soil was 0.50 m_ the soil was fertilized with nitrogen and tesis publicada con autorización del autor using a dosis of 5.20 kg of urea applying first half of the dosis and the second half after 30 days. The total rain precipitation during the experiment was 625. 1 o mm and the average temperature was 23.42 ºc. According to the obtained results and the statístical analysis we conclude that there are differences of the grain yield between the treatments at 14% of humidity, due to the genotypical differences. the yields fluctuated between 5787 kg/ha (címcali97bsa4-2) and 1908 kg/ha (cimcali96sa3). The variety cimcali97bsa4-2 overcomes in yield the varieties cimcali97asa4, inia 602 and pimte with 8.35%, 8.52% and 11 .65% respectively, however no statistically significant differences were found between these results.